Novel Quinazolinone–Isoxazoline Hybrids: Synthesis, Spectroscopic Characterization, and DFT Mechanistic Study - Yassine Rhazi; Mohammed Chalkha; Asmae Nakkabi; Imad Hammoudan; Mohamed Akhazzane; Mohamed Bakhouch; Samir Chtita; Mohamed El Yazidi (Chemistry, 2022)
Quinazolinone and isoxazoline systems have attracted much attention due to their interesting pharmacological properties. The association of these two pharmacophores in a single hybrid structure can boost the biological activity or bring a new one. Inspired by this new paradigm, in the present work we report the synthesis and spectroscopic characterization of new quinazolinone–isoxazoline hybrids. The target compounds were obtained via 1,3-dipolar cycloaddition reactions of arylnitriloxides and N-allylquinazolinone. The synthesized compounds were characterized using spectroscopic techniques such as IR, 1D NMR (1H and 13C), 2D NMR (COSY and HSQC), and high-resolution mass spectrometry (HRMS). The spectral data show that this reaction leads only to the 3,5-disubstituted isoxazoline regioisomer, and that the observed regiochemistry is not affected by the nature of the substituents in the phenyl ring of the dipole. In addition, a theoretical study was performed using density functional theory (DFT) to support the experimental results in regard to the regiochemistry of the studied reactions. The computational mechanistic study was in good agreement with the experimental data.